2009
DOI: 10.1007/s00122-009-1031-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and genetic mapping of pm42, a new recessive wheat powdery mildew resistance gene derived from wild emmer (Triticum turgidum var. dicoccoides)

Abstract: Powdery mildew, caused by Blumeria graminis f. sp. tritici, is one of the most important wheat diseases worldwide in areas with cool or maritime climates. Wild emmer (Triticum turgidum var. dicoccoides) is an important potential donor of disease resistances and other traits for common wheat improvement. A powdery mildew resistance gene was transferred from wild emmer accession G-303-1M to susceptible common wheat by crossing and backcrossing, resulting in inbred line P63 (Yanda1817/G-303-1 M//3*Jing411, BC(2)F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(74 citation statements)
references
References 23 publications
1
64
0
9
Order By: Relevance
“…Development of resistant germplasm to powdery mildew is based on interspecific hybridization and backcrossing (Murphy;Navarro;Leath, 2002;Navarro et EMARA, H. M. et al al., 2000). To date, 61 powdery mildew resistance genes, mapped to 43 loci (McIntosh;Yamazaki;Dubcovsky, 2008;He et al, 2009;Hua et al, 2009;Li;Fang;Zhang, 2009;Luo et al, 2009) have been identified and formally catalogued in wheat. However, some of the genes, derived from wild relatives, are difficult to use in wheat breeding because of linkage drag (Hospital, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Development of resistant germplasm to powdery mildew is based on interspecific hybridization and backcrossing (Murphy;Navarro;Leath, 2002;Navarro et EMARA, H. M. et al al., 2000). To date, 61 powdery mildew resistance genes, mapped to 43 loci (McIntosh;Yamazaki;Dubcovsky, 2008;He et al, 2009;Hua et al, 2009;Li;Fang;Zhang, 2009;Luo et al, 2009) have been identified and formally catalogued in wheat. However, some of the genes, derived from wild relatives, are difficult to use in wheat breeding because of linkage drag (Hospital, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…MlZec1, a dominant resistance gene derived from wild emmer, was mapped distally to SSR marker Xwmc356 in terminal bin 2BL 0.89-1.00 (Mohler et al 2005). Two recessive powdery mildew resistance genes, Pm26 and Pm42 from wild emmer were located on chromosome 2BS (Rong et al 2000;Hua et al 2009). Our integrated mapping results indicate that MlIW170 is 17.15 cM distal to Pm42 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…dicoccoides (2n = 4x = 28; genome AABB), the progenitor of cultivated tetraploid and hexaploid wheats, is rich in genetic diversity for resistances to powdery mildew (Moseman et al 1984). Several powdery mildew resistance genes, such as Pm16 (Reader and Miller 1991), Pm26 (Rong et al 2000), Pm30 (Liu et al 2002), MlZec1 (Mohler et al 2005), MlIW72 (Ji et al 2007), Pm36 (Blanco et al 2008), Pm41 (Li et al 2009), Pm42 (Hua et al 2009), PmG16 (Ben-David et al 2010, and Ml3D232 were identified in wild emmer, or transferred to cultivated wheat or cultivated wheat derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The sterility of the pentaploid hybrids is generally conquered by further crossing or backcrossing the hybrids with common wheat cultivars (AABBDD) (Liu et al, 2002, Brown-Guedira et al, 2005, Hua et al, 2009, Ogbonnaya and Abdalla, 2013. …”
Section: Genome Evolution and Domestication In Triticum Aestivummentioning
confidence: 99%